The Role of Parents in Forming the Character of Elementary School-Age Children - Indah Pratiwi; Melyani Sari Sitepu; Nurdiyah Nurdiyah (UMSU, 2023)
Parents are the first place for a child to get socialization regarding character education. Children spend more time at home with their parents, so that parents have the biggest contribution to character education in children. By providing character education to children from an early age, it will be useful for the child's life in the future. In making this article aims to get an overview of the role of parents in the formation of character in elementary school children. The method used in is a qualitative method. The subjects in this study were parents and students, the object of this study was the role of parents in character education for elementary school-age children. Character education aims to develop the potential to become human beings who have noble character, character education must continue over time character education is needed for each individual to become a better person and be able to uphold human values.